DETERMINANTS OF NON-MUSLIM COMMUNITY INTENTION TO PURCHASE HALAL-LABELED PRODUCTS - Syarifah Hayati; Darwis Harahap; Utari Cahyani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study aims to analyze the factors influencing non-Muslim consumers' purchasing interest in halal-labeled products in North Tapanuli Regency. The study used a descriptive quantitative approach involving 92 respondents and was analyzed using the SEM-PLS method. The results showed that understanding, price, and promotion directly influenced purchasing interest, while understanding and price influenced attitudes. However, attitudes did not act as a mediating variable in increasing purchasing interest. Therefore, this study recommends increasing halal education and setting competitive prices as the main strategies in expanding the market for halal products among non-Muslim consumers.